Pemberdayaan Pengrajin Gerabah Melalui Strategi Pemasaran Inovatif - Alienra Davry Nanda Kadun MT; Terianus Luther Safkaur; Ferry Rhendra Pananda Putra Sitorus (Pusat Riset dan Inovasi Nasional, 2025)
Abar Village is the only traditional pottery-producing village in Sentani that still survives today. This craft not only has economic value but also embodies the historical, social, and cultural values of the Sentani indigenous people. Amidst technological developments and the onslaught of modern products, Abar pottery continues to be produced using traditional methods passed down through generations, utilizing natural raw materials available around Lake Sentani. This uniqueness makes Abar pottery a cultural heritage worthy of preservation. However, the craftsmen face serious challenges, particularly in the areas of promotion and marketing, which are still very limited. Limited access to information, marketing networks, and the use of digital media are factors that hinder the development of Abar pottery businesses in a wider market. This community service program is designed to empower traditional pottery artisans in Abar Village, Jayapura Regency, with a focus on improving marketing knowledge and skills. Training activities include an introduction to modern marketing strategies, the use of social media for product promotion, product photography techniques, and the development of marketing narratives that highlight the cultural value and uniqueness of Abar pottery. The methods used included classical training, group discussions, and direct mentoring in creating promotional content. Initial results indicate an increase in artisans' understanding of marketing strategies and practical skills in utilizing digital platforms. Some artisans have begun implementing photography techniques and creating social media accounts to market their products. This program is expected to encourage the development of traditional pottery businesses, improve the welfare of the Abar Village community, and preserve its social and cultural values. The program's success could serve as a model for empowering a creative economy based on local wisdom in other regions.